Theoretical Perspectives on Adolescent Internet Addiction: A Comprehensive Literature Review. - Jin, Yishan; Jiang, Shan; Li, Chunkai (Health & Social Care in the Community, 2025)
The increasing reliance on the internet has intensified concerns about internet addiction, especially among adolescents. Previous studies have associated adolescent internet addiction with detrimental psychological conditions and deteriorating social bonds. Nonetheless, a comprehensive theoretical framework for understanding the development of adolescent internet addiction remains elusive, impeding the advancement of research focused on creating effective educational and intervention strategies. This study undertakes a systematic review of existing theories and models related to adolescent internet addiction, offering an integrated theoretical framework that aims to elucidate the underlying causes and mechanisms. Our proposed framework seeks to enhance the conceptual foundation for future research, thereby facilitating the development of targeted interventions.